Evaluation of the implementation of the Kurikulum Merdeka at SMAN 14 Bandung - Furqanisah Furqanisah; Zainal Arifin (Himpunan Pengembang Kurikulum Indonesia, 2024)
SMAN 14 Bandung is one of the schools implementing the Kurikulum Merdeka through active and collaborative learning. This research aims to evaluate the extent to which the objectives of implementing the Kurikulum Merdeka have been achieved at SMAN 14 Bandung. The assessment method used is descriptive qualitative. Data was collected through questionnaires and observations, then analyzed statistically using the mean and presented in graphs to facilitate understanding of the patterns. The study's results found that the evaluation of the Kurikulum Merdeka at SMAN 14 Bandung includes three main aspects: planning, implementation, and learning assessment. In the aspect of learning planning, teaching modules are developed according to the Learning Outcomes (CP) without modification, and the lesson planning is developed using innovative methods such as Problem-Based Learning (PBL) and Project-Based Learning (PjBL). The curriculum implementation utilizes school reference books, a deductive approach, and differentiated learning, with the PjBL method being quite popular among students. The assessment aspect of learning employs formative tests, summative assessments, portfolios, and projects to evaluate cognitive, affective, and psychomotor learning outcomes, along with diagnostic assessments conducted before the lessons. Abstrak SMAN 14 Bandung merupakan salah satu sekolah yang telah menerapkan Kurikulum Merdeka melalui pembelajaran aktif dan kolaboratif. Penelitian bertujuan untuk mengevaluasi sejauh mana efektivitas tujuan penerapan Kurikulum Merdeka telah di capai dalam perepannya di SMAN 14 Bandung. Metode penilaian menggunakan deskriptif kualitatif. Data dikumpulkan melalui kuesioner dan observasi, lalu dianalisis secara statistik menggunakan rata-rata (mean) dan disajikan dalam grafik untuk memudahkan pemahaman pola. Hasil penelitian ditemukan Evaluasi penerapan Kurikulum Merdeka di SMAN 14 Bandung mencakup tiga aspek utama: perencanaan, pelaksanaan, dan penilaian pembelajaran. Aspek perencanaan pembelajaran, modul ajar dikembangkan sesuai Capaian Pembelajaran (CP) tanpa modifikasi, perencanaan pembelajaran dikembangkan menggunakan metode inovatif seperti PBL dan PjBL. Pelaksanaan kurikulum memanfaatkan buku pegangan sekolah, pendekatan deduktif, dan pembelajaran diferensiasi, dengan metode PjBL yang cukup diminati siswa. Aspek penilaian pembelajaran menggunakan tes formatif, sumatif, portofolio, dan proyek untuk menilai capaian pembelajaran kognitif, afektif, dan psikomotorik, serta dilakukan penilaian diagnostik sebelum pembelajaran. Kata Kunci: asesmen; evaluasi kurikulum merdeka; implementasi; perencanaan pembelajaran